A Case of Bronchial Artery Aneurysm Incidentally Discovered as a Pulsatile Oesophageal Submucosal Mass - Ibuki Kosai; Masahiro Kawashima; Kengo Sato; Tadahisa Wada; Keita Takeda; Takafumi Kato; Hiroshi Igei; Kimihiko Masuda; Yoshiteru Morio; Hirotoshi Matsui (Respirology Case Reports)
ABSTRACT Bronchial artery aneurysm (BAA) is often detected through haemoptysis or chest pain, and its rupture can be life‐threatening. However, due to the rarity of BAAs, the optimal management of unruptured cases remains uncertain. Here, we report a case of an asymptomatic BAA that was incidentally discovered and successfully treated with bronchial artery embolization (BAE). The BAA was identified during an upper gastrointestinal endoscopy performed as a follow‐up after Helicobacter pylori eradication, where a pulsatile oesophageal submucosal mass was observed. The diagnosis of BAA was subsequently confirmed by contrast‐enhanced CT. BAE was performed using metallic coils, and the patient has since remained stable, with no occurrence of haemoptysis. BAE for unruptured BAA may prevent rupture and thereby avert potentially fatal outcomes.